EXPERIENCE OF SURGICAL TREATMENT OF PROLIFERATIVE DIABETIC RETINOPATHY - O. M. Trubina; V. N. Kanyukov; A. N. Kazennov; I. A. Kazennova (Acta Biomedica Scientifica)
The study included 48 vitreoretinal surgeries performed during 2014-2015 in 39 patients with advanced fibrovascular stage of proliferative diabetic retinopathy. Visual acuity before the surgery averaged from pr. l. certae to 0.01. In 7 cases patients underwent intravitreal injection of Lucentis 2-3 weeks before the surgery. The surgery was performed according to the standard 3-port 25 G vitrectomy. In some cases, short-term tamponade of vitreous cavity by fluid perfluororganic compounds (PFOS) was performed for 2-3 days. This was due to prolonged bleeding during the surgery. In these cases, fibrinolytic of direct action (hemasa) was injected directly to the blood clot. In 4 cases circular retinotomy was needed. In 35 cases tamponade was made by silicone oil 5700 cSt, in 13 - by air-gas mixture. In cases of air-gas tamponade 3 patients had a relapse. After vitreous cavity revision it was plugged with silicone oil 5700 cSt. In 17 cases visual function remained unchanged, in 18 cases the changes were imperceptible, in 9 cases visual acuity improved to 0.2, in 3 cases -visual function increased to 0.4 and in 1 patient - to 0.7. In postoperative period IOP increased in 7 cases. In 5 of these cases compensation was achieved with antihypertensive drugs. 1n one case the patient was implanted leukosapphire drainage, and in one more case transscleral cyclophotocoagulation about terminal aching glaucoma was performed. The silicone oil was removed in 6 patients at the period of 6 months up to 2 years.